2009
DOI: 10.1055/s-0029-1214242
|View full text |Cite
|
Sign up to set email alerts
|

Reference Range of Urinary Neutrophil Gelatinase-Associated Lipocalin in Very Low-Birth-Weight Infants: Preliminary Data

Abstract: We sought to determine the reference range for urinary neutrophil gelatinase-associated lipocalin (UNGAL) in very low-birth-weight (VLBW) infants with uncomplicated clinical courses. Samples of urine from 53 VLBW infants between 3 and 28 days of life were prospectively collected weekly for measurement of UNGAL. A subset of 22 infants with uncomplicated medical courses without risk factors for renal impairment was selected for study. Mean +/- standard deviation and range for birth weight and gestational age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 6 publications
2
18
1
1
Order By: Relevance
“…Compared to previous reports the strengths of this study are a larger patient population, the daily urine collections for the first month of life in a portion of the study population, and exclusion of VLBW infants with complicated courses. This report provides normative UNGAL concentrations, further refining the preliminary data from a study of 22 infants with uncomplicated courses that we previously reported (25). No patients < 26 weeks gestation or birth weight ≤ 750 grams in this sample had uncomplicated clinical courses.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Compared to previous reports the strengths of this study are a larger patient population, the daily urine collections for the first month of life in a portion of the study population, and exclusion of VLBW infants with complicated courses. This report provides normative UNGAL concentrations, further refining the preliminary data from a study of 22 infants with uncomplicated courses that we previously reported (25). No patients < 26 weeks gestation or birth weight ≤ 750 grams in this sample had uncomplicated clinical courses.…”
Section: Discussionsupporting
confidence: 71%
“…This is the third report of UNGAL concentrations in VLBW infants (25,28). Compared to previous reports the strengths of this study are a larger patient population, the daily urine collections for the first month of life in a portion of the study population, and exclusion of VLBW infants with complicated courses.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The results showed that, uNGAL levels in the current study were higher than the recently reported standard value in VLBW infants (15,25). This difference may be explained by the fact that there were many premature infants with a gestational age <27 weeks among our subjects.…”
Section: Discussioncontrasting
confidence: 78%
“…8,9), and its protein appeared in the urine and in the serum (5-to 500-fold increase) within hours of stimuli that typically cause acute kidney injury (AKI). Inductive stimuli included sepsis (10)(11)(12)(13)(14), ischemia-reperfusion injury (IR) (9,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), obstructive uropathy (28), nephrotoxins (15,(29)(30)(31)(32)(33), traumarhabdomyolysis (34), kidney graft injury (35,36), or a mixture of these maladies (37,38). Sepsis was a particularly strong stimulus for LCN2 expression.…”
Section: Introductionmentioning
confidence: 99%